JOB SATISFACTION: THE APPLICATION OF THE LEADERSHIP MINDSET FOR SMALL BUSINESSES PERFORMANCE - ANNAN, DAVID (Digital Repository of Theses - SSBM Geneva, 2021)
Critical decision-making is a backbone for the success of many businesses. Small business leaders continually make such decisions with the inadequacy of resources to ensure the company's floating against large corporations. Kovacs et al. (2017) indicated that most small businesses lack strategies to maintain professional communication and plan to increase job satisfaction between leaders and employees. This study explores the leadership mindset and strategies to help develop small businesses and bring job satisfaction for both the employer and the employee. The study used a qualitative case method to provide insights into a problem and help develop hypotheses for the study. The target population was twenty-five small business leaders in Astana, Kazakhstan, with sprawling companies in Kazakhstan's capital city. Purposive sampling was applied using semi-structured in-depth interviews to advance job satisfaction strategies Data were analyzed using inductive coding of phrases and word frequency searches to create a thematic analysis. The triangulation approach was used to cross-validate and strengthened the study's reliability. The study's findings could be valuable to micro and small businesses as they might fill the gap in understanding strategies to increase job satisfaction.